2022
DOI: 10.3389/fsurg.2022.1018030
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality hologram combined with pre-bent distractor enhanced the accuracy of distraction vector transfer in maxillary distraction osteogenesis, a study based on 3D printed phantoms

Abstract: BackgroundVector control is a significant concern in maxillary distraction osteogenesis (DO). Distraction vector planning on the patient's 3D-printed skull phantom is more intuitive for surgeons and cost-efficient than virtual surgical planning. However, the accuracy of transferring the planned vector to intraoperative (vector transfer) according to the shape of the pre-bent footplate alone is relatively limited. The application of augmented reality (AR) in surgical navigation has been studied for years. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Augmented reality (AR) surgical navigation has been used specifically for improved vector planning in maxillary distraction. 66 Yuan et al found that using 3D-printed skull phantoms with AR surgical navigation enhanced the accuracy of the distraction vector when compared to standard virtual surgical planning. 66…”
Section: Midface (Maxilla)mentioning
confidence: 99%
See 1 more Smart Citation
“…Augmented reality (AR) surgical navigation has been used specifically for improved vector planning in maxillary distraction. 66 Yuan et al found that using 3D-printed skull phantoms with AR surgical navigation enhanced the accuracy of the distraction vector when compared to standard virtual surgical planning. 66…”
Section: Midface (Maxilla)mentioning
confidence: 99%
“…66 Yuan et al found that using 3D-printed skull phantoms with AR surgical navigation enhanced the accuracy of the distraction vector when compared to standard virtual surgical planning. 66…”
Section: Midface (Maxilla)mentioning
confidence: 99%